A Multi-Modal haptic interface for Virtual Reality and Robotics - Folgheraiter, Michele; Gini, Giuseppina; Vercesi, Dario (Journal of Intelligent and Robotic Systems, 2008)
In this paper we present an innovative haptic device that combines the electro-tactile stimulation with the force and visual feedbacks in order to improve the perception of a virtual world. We discuss about the sensation evoked in a user by the haptic, force, and visual interface provided by this device, implemented as a special glove, equipped with sensors and actua- tors connected to a PC. The techniques used to recreate tactile and kines- thetic sensations are based on an innovative use of cutaneous stimulation integrated with actuators and 3D modelling techniques. We discuss about the specificity of haptic interfaces, their controllers, their open problems. We present results about generating the sensation of touching virtual ob- jects with our device. Experiments show also that, using a multi-modal sensorial pattern of stimulation, the subject perceives more realistically the virtual object. We discuss about possible use of the same technique as a way to interface intelligent robots.
Keywords: Virtual Reality; Electro-tactile Stimulation; Haptic Devices; Robotic Grasp; Haptic display